2007
DOI: 10.1073/pnas.0704497104
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of Haldane's hypothesis on the role of infection as an evolutionary force for Metazoans

Abstract: A common drawback in evolutionary science is the fact that the evolution of organisms occurs in geological timing, completely out of the time scale of laboratory experimental work. For this reason, some relevant hypotheses on evolution of Metazoans are based on correlations more than on experimental data obtained for testing the robustness of those hypotheses. In the current work, we implement an experimental methodology to analyze the role of infections as a driving force in the evolution of Metazoans (Haldan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Most of these infections are clonal [24], and infections are acquired independently by each patient, presumably from diverse environmental reservoirs [25]. It has been suggested that there are not strong differences in the genetic structure or in the physiology of the different P. aeruginosa strains [15,26] and that the same factors are used to infect humans, plants, and nematodes [27,28]. Nevertheless, the level of expression of the different virulence determinants is different for bacteria producing acute (the most clear example is blood infection) or chronic (e.g., CF) infections, and it has been reported that genes associated with acute infection and chronic persistence in P. aeruginosa are reciprocally regulated [29].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these infections are clonal [24], and infections are acquired independently by each patient, presumably from diverse environmental reservoirs [25]. It has been suggested that there are not strong differences in the genetic structure or in the physiology of the different P. aeruginosa strains [15,26] and that the same factors are used to infect humans, plants, and nematodes [27,28]. Nevertheless, the level of expression of the different virulence determinants is different for bacteria producing acute (the most clear example is blood infection) or chronic (e.g., CF) infections, and it has been reported that genes associated with acute infection and chronic persistence in P. aeruginosa are reciprocally regulated [29].…”
Section: Discussionmentioning
confidence: 99%
“…The assay for studying bacterial killing of C. elegans was performed as described previously (25). Briefly, a fresh culture of each bacterial strain to be tested was layered onto a 55-mm-diameter plate containing 5 ml of potato dextrose agar.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, given the time required for the evolution of Metazoans ( Navas et al 2007), emergence and spread of resistance is considered as one of the few evolutionary processes that can be studied in real time (Salmond & Welch 2008). In spite of these considerations, the recent use (in evolutionary terms) of antibiotics for human therapy and farming is not the unique force driving evolution towards antibiotic resistance of human pathogens.…”
Section: Intrinsic Resistancementioning
confidence: 99%